Redox Control and Hydrogen Production in Sediment Caps Using Carbon Cloth Electrodes - Sun, Mei (2010)
Sediment caps that degrade contaminants can improve their ability to contain contaminants relative to sand and sorbent-amended caps, but few methods to enhance contaminant degradation in sediment caps are available. The objective of this study was to determine if, carbon electrodes emplaced within a sediment cap at poised potential could create a redox gradient and provide electron donor for the potential degradation of contaminants. In a simulated sediment cap overlying sediment from the Anacostia River (Washington, DC), electrochemically induced redox gradients were developed within 3 days and maintained over the period of the test (~100 days). Hydrogen and oxygen were produced by water electrolysis at the electrode surfaces and may serve as electron donor and acceptor for contaminant degradation. Electrochemical and geochemical factors that may influence hydrogen production were studied. Hydrogen production displayed zero order kinetics with ~75% coulombic efficiency and rates were proportional to the applied potential between 2.5V to 5V and not greatly affected by pH. Hydrogen production was promoted by increasing ionic strength and in the presence of natural organic matter. Graphite electrode-stimulated degradation of tetrachlorobenzene in a batch reactor was dependent on applied voltage and production of hydrogen to a concentration above the threshold for biological dechlorination. These findings suggest that electrochemical reactive capping can potentially be used to create “reactive” sediments caps capable of promoting chemical or biological transformations of contaminants within the cap.